2022
DOI: 10.1109/ted.2022.3186869
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Investigation of Wake-Up in High Endurance Fatigue-Free La and Y Doped HZO Metal–Ferroelectric–Metal Capacitors

Abstract: High endurance of 10 11 cycles is demonstrated in ~9-10nm stoichiometric HZO metalferroelectric-metal (MFM) capacitors deposited using Cl precursors with La and Y dopants. La doping is shown to offer higher remnant polarization than Y. Investigation of doped layers with asymmetric polarization versus electric field (P-E) measurements and unipolar fatigue cycles suggest that in pristine state, the HZO is comprised of ferroelectric domains with internal built-in electric field induced pinned coercive field (Ec).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Moreover, maintaining the same amount of trivalent dopant atoms (corresponding to three cycles of ALD) and distributed in a smaller volume of hafnium zirconate in the case of thinner (9.5 nm) HZO films possibly induce a higher density of oxygen vacancies that can be held responsible for a stronger internal bias field. During the electrical cycling, the local density of oxygen decreases and/or the oxygen vacancies rearrange in a more uniform manner within the ferroelectric sandwiched between TiN electrodes, both previously associated to the wake-up effect. The initial 2P r was found to decrease in the order 3La > 2La + Y > 2Y + La > 3Y (Figure ).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Moreover, maintaining the same amount of trivalent dopant atoms (corresponding to three cycles of ALD) and distributed in a smaller volume of hafnium zirconate in the case of thinner (9.5 nm) HZO films possibly induce a higher density of oxygen vacancies that can be held responsible for a stronger internal bias field. During the electrical cycling, the local density of oxygen decreases and/or the oxygen vacancies rearrange in a more uniform manner within the ferroelectric sandwiched between TiN electrodes, both previously associated to the wake-up effect. The initial 2P r was found to decrease in the order 3La > 2La + Y > 2Y + La > 3Y (Figure ).…”
Section: Results and Discussionmentioning
confidence: 99%
“…There have been suggestions that AFE behavior may be the result of charged ionic defects and pinned ferroelectric or ferroelastic domains, rather than reversible electric field-induced phase transitions. [33][34][35] The apparent device-terminal similarities and the fluid transformation of pinched to square FE hysteresis loops with field cycling, commonly called "wake-up", in fluoritestructured FEs further add to the confusion. [33][34][35] The challenge of distinguishing between FE and AFE in fluorite-structured materials, which is critical for advancing technology, stems from not one but several experimental limitations: i) The FE polar orthorhombic (o) Pca2 1 phase is structurally similar to the nonpolar tetragonal (t) P4 2 /nmc phase, obfuscating clear identification of the phases in thin films by grazing incidence x-ray diffraction (GIXRD).…”
Section: Distinguishing Afe Zro 2 From Pinched Fe La-doped Hfomentioning
confidence: 99%
“…There are different mechanisms reported that can contribute to the wake-up effect such as domain depinning from defect redistribution and field-induced structural transformation from the tetragonal (T-) phase to the ferroelectric orthorhombic (O-) phase. [10][11][12][13][14] Qi et al used DFT calculations to investigate the energy barriers to polymorphic phase transitions in HfO 2 -based ferroelectric crystals, including the effect of applied electric As an emerging nonvolatile memory technology, HfO 2 -based ferroelectrics exhibit excellent compatibility with silicon CMOS process flows; however, the reliability of polarization switching in these materials remains a major challenge. During repeated field programming and erase of the polarization state of initially pristine HfO 2 -based ferroelectric capacitors, the magnitude of the measured polarization increases, a phenomenon known as "wake-up".…”
Section: Introductionmentioning
confidence: 99%
“…There are different mechanisms reported that can contribute to the wake‐up effect such as domain depinning from defect redistribution and field‐induced structural transformation from the tetragonal (T‐) phase to the ferroelectric orthorhombic (O‐) phase. [ 10–14 ]…”
Section: Introductionmentioning
confidence: 99%